EVALUASI PELAKSANAAN MANAJEMEN LAKTASI DAN INISIASI MENYUSU DINI (IMD) DI RUMAH SAKIT UMUM DAERAH Dr. PIRNGADI KOTA MEDAN PROVINSI SUMATERA UTARA - , Aureliya Hutagaoll ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Lactation Management and Early Initiation of Breastfeeding (EIB) strongly supports the optimum and maximum achievement of exclusive breastfeeding. Scope of exclusive breastfeeding targeted in the National Development Program and the National Strategy (PP-ASI) is 80%. In accordance with the Millennium Development Goals (MDGs) program to help reduce poverty, hunger, and infant mortality. It is important to convey information about lactation management and EIB to the antenatal, intranatal, and postnatal mothers and health workers in order to carry out professional duties as a promoter in the use of breast milk. Objective: To perform the evaluation of lactation management and EIB implementation and the supporting and inhibiting factors in room V Tanjung, Neonati, antenatal polyclinic, Dr. Pirngadi Hospital, Medan. Methods: The research method was qualitative but the research was presented descriptively. The data were analyzed with the Interactive Model. The sources of data derived from in-depth interviews and document and open participant observations. Results: The evaluation of lactation management was carried out in accordance with the standards. However, the implementation of the EIB had not reached the optimum results, with respect to the lack of deep knowledge about EIB and its implementation had not been in accordance with the recommended theory of EIB. EIB Promotion had not been performed due to the absence of leaflets / brochures and Rooming In and the presence of the role of infant formula. Related to the lack of task coordination clarity for midwives / nurses in implementing the EIB, the increase in quality of health workers should be done through training and provision of posters / leaflets in favor of lactation and EIB management. Conclusion: The management of lactation remained improved and maintained but EIB had not been in accordance with the recommended implementation.